Hypoxia: Progressive Multiple Myeloma and Its Therapy Resistance - Ogechi Charity Obayi; Emmanuella Ogbonna; Catherine Chinonye Eleje; Nwabueze Enukaorah Permsec Umerah (Research Center for Rational Use of Drugs (RCRUD), 2021)
This study critically reviews the role of hypoxia in the progression of Multiple Myeloma (MM)and its therapy resistance. It explains the existence and role played by Hypoxia Inducible Factors (HIF) including HIF-1α and HIF-β in tumor (MM) progression. These HIF are key transcription factors of hypoxia and they aid the cellular adaptation of both normal and cancer cells to reduction in oxygen concentration. At initial stage of MM, the bone marrow environment sufﬁciently supports the growth and survival of the MM cells, but as the disease progresses and the plasma cells goes deeper into the bone marrow, they experience a more hypoxic condition. This then activates HIF-1 and HIF-2 which ultimately stimulates angiogenic factors. This is a description of the step by step approaches through which a review of Hypoxia: progressive multiple myeloma and its drug resistance was conducted using Google scholar and PubMed search engines to search articles published from 2000 to May 2020 using the following key words: hypoxia, progressive multiple myeloma, treatment resistance, hypoxia and multiple myeloma. This review suggests that agents capable of inhibiting the action of HIF's, as well as those that would act speciﬁcally on the hypoxic zones will be helpful in minimizing/eliminating drug resistance and relapses in MM patients and would invariably improves the patient life expectancy.